Research progress in traditional Chinese medicine in the treatment of Alzheimer's disease and related dementias - Wanying Tan; Lingjun Qi; Xiaoyu Hu; Zhenghuai Tan (Frontiers Media S.A., 2022)
Alzheimer's disease (AD) is the world's leading cause of dementia and has become a huge economic burden on nations and families. However, the exact etiology of AD is still unknown, and there are no efficient medicines or methods to prevent the deterioration of cognition. Traditional Chinese medicine (TCM) has made important contributions in the battle against AD based on the characteristics of multiple targets of TCM. This study reviewed the treatment strategies and new discoveries of traditional Chinese medicine in current research, which may be beneficial to new drug researchers.